Individual Retirement Accounts - Rachel Dorman; Lisa M. Leslie; Michael S. Gutter; Martie Gillen; Josephine Turner (EDIS, 2012)
An individual retirement account (IRA) is a good tool to build retirement funds. This type of account has been offered since 1974 and comes with special tax advantages. An IRA can be opened through a financial institution such as a bank, credit union, mutual fund company, or brokerage firm. Learn more in this revised 4-page fact sheet written by Rachel Dorman, Lisa M. Leslie, Michael S. Gutter, Martie Gillen, and Josephine Turner, and published by the UF Department of Family, Youth and Community Sciences, April 2012.